2019
DOI: 10.1002/art.40792
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Disease Activity in Systemic Lupus Erythematosus With Single‐Molecule Array Digital Enzyme‐Linked Immunosorbent Assay Quantification of Serum Interferon‐α

Abstract: Objective. No simple or standardized assay is available to quantify interferon-α (IFNα) in routine clinical practice. Single-molecule array (Simoa) digital enzyme-linked immunosorbent assay (ELISA) technology enables direct IFNα quantification at attomolar (femtogram per milliliter [fg/ml]) concentrations. This study was undertaken to assess IFNα digital ELISA diagnostic performances to monitor systemic lupus erythematosus (SLE) activity.Methods. IFNα concentrations in serum samples from 150 consecutive SLE pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 52 publications
(78 reference statements)
4
51
1
Order By: Relevance
“…The area under the ROC curve for IFNα concentration as a discriminator of active versus inactive juvenile IIM was 0.81 (95% confidence interval 0.70-0.92) ( Figure 1D). This value is close to the value of 0.83 previously described in SLE patients by Mathian et al (1). To distinguish active versus inactive juvenile IIM, the optimal cutoff threshold for IFNα concentration was 41.7 fg/ml, with a sensitivity and specificity of 76% and 81%, respectively (Youden index 0.57).…”
Section: To the Editorsupporting
confidence: 84%
See 1 more Smart Citation
“…The area under the ROC curve for IFNα concentration as a discriminator of active versus inactive juvenile IIM was 0.81 (95% confidence interval 0.70-0.92) ( Figure 1D). This value is close to the value of 0.83 previously described in SLE patients by Mathian et al (1). To distinguish active versus inactive juvenile IIM, the optimal cutoff threshold for IFNα concentration was 41.7 fg/ml, with a sensitivity and specificity of 76% and 81%, respectively (Youden index 0.57).…”
Section: To the Editorsupporting
confidence: 84%
“…We read with interest the report by Dr. Mathian and colleagues in which they suggested that direct serum interferon-α (IFNα) determination with a highly sensitive assay might be useful for disease activity monitoring in systemic lupus erythematosus (SLE) (1). More generally, the identification of reactive biomarkers is highly desirable in many disease states, including idiopathic inflammatory myopathies (IIMs).…”
Section: To the Editormentioning
confidence: 99%
“…Transcriptome analysis using microarray technology revealed upregulation of the expression of numerous IFN-stimulated genes (ISGs) in SLE patients’ peripheral blood mononuclear cells, constituting an overall ‘IFN signature’ 17 18. Many reports showed patients’ elevated serum-IFN-α levels to be associated with SLE activity and severity, suggesting that monitoring this cytokine might help physicians to better evaluate disease activity,17–35 although, unexpectedly, some clinically inactive patients have persistently elevated serum IFN-α levels 19–23 25 35. Since serum concentrations of IFN-α are usually very low and often not detectable by classic immunoassays, monitoring the expression of ISGs is used to evaluate IFN serological activity.…”
Section: Introductionmentioning
confidence: 99%
“…The single-molecule array (Simoa) assay, or digital immunoassay, is an ultrasensitive assay based on enumeration of individual enzyme-labelled immunocomplexes of proteins captured on beads in single-molecule arrays. It enables direct IFN-α quantification at attomolar concentrations,35 38–40 corresponding to a 5000-fold—increased sensitivity over classic ELISAs. We and others have shown that, at physiological concentrations, the digital immunoassay is as sensitive as ISG expression as a means to quantify IFN-α levels and simpler to perform and standardise 35 40.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, there was a positive correlation between tADA activity and SLE disease activity, which suggested that tADA activity might be helpful in monitoring the disease activity. Several studies have reported that interferon level (such as IFN-1α, IFN-α and IFN-λ3) were increased in SLE patients [21][22][23], which suggested the change of interferon signature were involved in SLE development. We will investigate the potential association between ADA activity and interferon in SLE patients in further study.…”
Section: Controlmentioning
confidence: 99%